PENINGKATAN KEMAMPUAN BINA DIRI MEGGOSOK GIGI MELALUI METODE TEACCH PADA ANAK AUTIS KELAS IV DI SLB NEGERI 1 MAROS - Nurrah Fatun; Syamsuddin; Dwiyatmi Sulasminah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses a practical issue involving a fourth-grade student with autism who was unable to brush their teeth independently—particularly the inner surfaces—and thus required assistance at every stage of the activity. The study aimed to determine the improvement in self-care skills (specifically tooth brushing) achieved through the TEACCH method for a fourth-grade student with autism at SLB Negeri 1 Maros. A quantitative approach was employed using a Single-Subject Research experimental method with an A-B-A design. The subject was a student with autism identified by the initial 'A'. Data were analyzed using visual analysis, encompassing both within-condition and between-condition analyses. The results indicated that the student's tooth-brushing self-care skills fell into the low category during the Baseline-1 (A1) phase. Following the intervention using the TEACCH method (Phase B), the student's tooth-brushing ability improved. This improvement was sustained during the Baseline-2 (A2) phase, even after the intervention had ceased. Based on the between-condition analyses (A1-B and B-A2), the TEACCH method positively influenced the improvement of tooth-brushing skills in the fourth-grade student with autism at SLB Negeri 1 Maros.